Porcine salivary carbonic anhydrase VI is involved in the pathogenesis of disease - Matas-Quintanilla, M.; López-Balibrea, R. I.; Miller, I.; Gutiérrez, A. M. (Frontiers in Veterinary Science, 2026)
IntroductionEvidence exists of the role of salivary carbonic anhydrase VI (CA VI) in the protection of the oral mucosa and in the gastrointestinal and respiratory tracts in different species. However, little is known of the behaviour of CA VI in porcine disease. We aimed to study the behaviour of salivary CA VI in porcine stress and disease for the first time, and to study the concentrations of the CA VI in different homeostasis disturbances under field disease conditions.Material and methodsWe used saliva samples from 30 healthy pigs and 30 pigs with different disorders in a validation trial using protein separation and specific CA VI detection. Afterwards, the salivary CA VI concentrations of 255 clinically healthy pigs and 371 pigs with different signs of disease were quantified using a new in-house immunoassay in a field trial in which salivary alpha amylase and C-reactive protein (CRP) levels were also evaluated.ResultsThe overall specific CA VI signal appeared increased in disease conditions in comparison to the healthy state, whilst stress showed no statistical modification. The immunoassay developed for CA VI quantification showed good analytical performance and revealed increased concentrations in all the diseases studied in comparison to healthy animals, with pronounced intensities in gastrointestinal and respiratory diseases, followed by animals with inflammatory conditions. CA VI showed a moderate positive association with alpha amylase and a low but positive association with CRP.DiscussionThe present findings suggest that salivary CA VI is involved in the pathogenesis of disease in pigs with an increase in its concentrations; however, the specific roles attributed to CA VI in disease conditions should be further studied.